TOPLUMSAL CİNSİYET ALGISI, DİN VE KADIN - Karakaya, Handan (Özcan GÜNGÖR, 2018)
ÖzetToplumsal Cinsiyet(Gender) tarih boyunca ve günümüzde kadının toplumsal konumunun biçimlenmesinde önemli bir faktör olarak kabul edilmektedir. İnsan bir birey olarak doğduğu toplumda cinsiyet algısına göre biçimlenmiş bir toplumsallaşma süreciyle baş başa kalmaktadır. Bu toplumsallaşma süreci cinsiyet alanları üzerinden biçimlendirildiği için kadınlar ve erkekler açısından farklı anlamlar ifade etmektedir. Bu süreçte kadınlar daha edilgen ve kamusal alanın dışında bir hayat için hazırlanmaktadırlar. Erkekler ise kamusal alana hâkim ve yöneten bir kimlikte tanımlanmaktadırlar. Bu ayrım tarihi süreç içerisinde, farklı toplumlarda farklı biçimlerde varlığını korumuştur. Değişen yaşam koşulları ve modernleşme süreci bu yaklaşım değişmesinde etkili olmakla birlikte ortadan kaldırıcı bir etkisinin olduğunu söylemek zordur.  Toplumda kadın ve erkekler arasındaki ayrımın derinliği, toplumsal cinsiyet algılarının gücü bağlamında derinleşebilmektedir. Kadınlar ve erkekler biyolojik cinsiyet (sex) farklılıklarının ötesinde sınırları keskince belirlenmiş sosyokültürel kalıplara zorlanmaktadırlar. Dolayısıyla toplumsal cinsiyet algısını besleyen unsurlar bu noktada önem kazanmaktadır. Bu çalışmanın amacı, toplumsal cinsiyeti besleyen tüm unsurlara görünürlük kazandırmak değildir. Çalışmada amacımız toplumsal yapının ve kültürün biçimlenmesinde önemli bir kaynak olan din ve toplumsal cinsiyet algısı arasındaki etkileşimin biçimini ortaya koymaktır. Bu açıdan ilkel dinlerden ilahi dinlere kadar cinsiyet kalıplarının ortaya çıkış biçimi ve korunma şekilleri üzerinde durulacaktır. Ancak bu makalenin sınırları içerisinde tüm dinler ve ortaya koydukları cinsiyet kalıplarını ele almak mümkün değildir. Aynı biçimde konuyla ilgili tüm kaynakların bu makalenin sınırları içerisinde ele alınması zordur. Bununla beraber başta  üç semavi din ve bunun dışında öne çıkan inanç biçimlerinin(Budizm, Hinduizm vb) kadın algısı kutsal metinler üzerinden ele alınacaktır.  Bu bağlamda genel bir çerçevenin ortaya konulması önemlidir. Bunun bize, dinin kadın algısı ve bu algının toplumsal cinsiyet algısına etkisini ortaya koyabilmek açısından bir perspektif sunabileceği kanısındayız. Bu alanda çalışan birçok uzman dinlerin kadınları erkeklerin gerisinde varlıklar olarak tanımlamadığını ifade eder. Ancak yapılan çalışmalar, gerek metinlerin yorumlanış biçiminin gerekse ataerkil toplumsal yapının kadının algısına etkisinin büyük olduğunu ortaya koymaktadır.  Bu algılamaya bağlı olarak kadınlar birçok ayrımcılığa uğradığa uğramakta ve kamusal alnın dışında kalmaktadırlar. Bu ayrımcılık dini metin ve sözlü anlatımlara dayandırılarak meşrulaştırılmaktadır. Dolayısıyla din yada toplumsal cinsiyet algısı kullanılarak kadın kamusal alnın dışına itildiği gibi toplumsal hayatta görünürlüğü büyük oranda engellenmektedir.Anahtar Kelimeler: Din, Kadın, Cinsiyet, Toplumsal Cinsiyet,ToplumSummary                    Gender (Gender) is accepted as an important factor throughout history and today in shaping women's social position. In a society where human beings are born as an individual, they are kept apart by a process of socialization divided by gender. This socialization process has different meanings for women and menn this process, women are preparing for a life that is more passive and out of public space. Men are defined by an identity that dominates and manages the public sphere. This distinction preserves its existence in different forms in different societies in the course of history. It is difficult to say that the changing living conditions and the modernization process are influential in this change of approach and have a lifting effect. The depth of the distinction between men and women in the society can deepen in the context of the power of gender perceptions. Women and men are struggling with socio-cultural patterns that are sharply defined beyond their biological sex differences. Therefore, the elements that feed the perception of gender are gaining importance at this point. The purpose of this study is not to give visibility to all elements that feed gender. Our aim in our work is to reveal the form of interaction between religion and gender perception, which is an important source of social structure and culturel formation. At this point, the way in which gender stereotypes emerged from primitive religions to divine religions will be emphasized. At this point, sacred texts of religions will be utilized It is difficult for all resources related to the topic to be handled within the limits of this article. However, the three sensual religions, and other forms of belief (Buddhism, Hinduism, etc.) that stand out, will be handled through sacred texts. We believe that this is a religious woman's perception and that it can offer an angle in terms of showing its effect on gender perception. Many experts who work in this area say that religions do not define women as being behind men. Studies have shown that the interpretation of the texts, or the patriarchal social structure, is largely influenced by women's perceptions. Due to this perception, women are undergoing many discriminations and are out of public awareness. Therefore, the woman is pushed out of the public sphere by using religion or gender perception. Key Words: Religion, Woman, Sex, Gender,Society

Gender (Gender) is accepted as an important factor throughout history and today in shaping women's social position. In a society where human beings are born as an individual, they are kept apart by a process of socialization divided by gender. This socialization process has different meanings for women and menn this process, women are preparing for a life that is more passive and out of public space. Men are defined by an identity that dominates and manages the public sphere. This distinction preserves its existence in different forms in different societies in the course of history. It is difficult to say that the changing living conditions and the modernization process are influential in this change of approach and have a lifting effect. The depth of the distinction between men and women in the society can deepen in the context of the power of gender perceptions. Women and men are struggling with socio-cultural patterns that are sharply defined beyond their biological sex differences. Therefore, the elements that feed the perception of gender are gaining importance at this point. The purpose of this study is not to give visibility to all elements that feed gender. Our aim in our work is to reveal the form of interaction between religion and gender perception, which is an important source of social structure and culturel formation. At this point, the way in which gender stereotypes emerged from primitive religions to divine religions will be emphasized. At this point, sacred texts of religions will be utilized It is difficult for all resources related to the topic to be handled within the limits of this article. However, the three sensual religions, and other forms of belief (Buddhism, Hinduism, etc.) that stand out, will be handled through sacred texts. We believe that this is a religious woman's perception and that it can offer an angle in terms of showing its effect on gender perception. Many experts who work in this area say that religions do not define women as being behind men. Studies have shown that the interpretation of the texts, or the patriarchal social structure, is largely influenced by women's perceptions. Due to this perception, women are undergoing many discriminations and are out of public awareness. Therefore, the woman is pushed out of the public sphere by using religion or gender perception.
PERCEPTION OF GENDER, RELIGION AND WOMEN
Keywords: Religious Studies; Din Araştırmaları